A developmental understanding of the self may provide valuable insight into the experience of selfhood in dementia. Issue 1 (22nd November 2022) - Mentzou, Aikaterini; Ross, Josephine
Abstract: The self is a complex and multidimensional construct with both reflective and experiential aspects. The experience of selfhood has been well documented in both developmental psychology and dementia research. However, these research fields have rarely come together. This is unfortunate since a lack of sensitive measurement of self in adults with dementia has historically led to erroneous assumptions that people diagnosed with dementia experience total loss of self. Dementia causes profound self‐alterations, particularly associated with gaps in autobiographical and semantic self‐knowledge. However, important experiential manifestations of self may remain intact. Focusing on the emergence of different levels of self‐processes in early childhood, and reflecting on conceptual similarities as well as methodological perspectives, the aim of this article is to explore how developmental approaches may be applied to provide a promising new direction into the experience of selfhood in dementia.